Odpowiedzi

2009-10-07T16:33:43+02:00
C) -2x*(-3xy)= 6x kwadrat y
d) x-x/2 - x/3= 3x-3x-2x/6 = - 2x/6
e) -4 * (-x/2) * (- 2x/4)= -4 * 2x kwadrat/8 = - 2xkwadrat / 2
= - x kwadrat
g) -(x+1) + (2x+4)= -x -1 +2x + 4 = x + 3
h) 3(a kwadrat - 4)-(-a kwadrat+ 2)= 3a kwadrat - 12 + a kwadrat -2 = 4 a kwadrat - 14
2009-10-07T16:36:35+02:00
Oblicz:
c) -2x*(-3xy)= 6x²y

d) x-x/2 - x/3 |*6
6x-3x-2x=x

e) -4 * (-x/2) * (- 2x/4) |*4
-16 * (-2x) * (-2x) = -64x²

g) -(x+1) + (2x+4)
-x - 1 + 2x + 4 = x-3

h) 3(a² - 4)-(-a² + 2)
3a² - 12 + a² - 2 = 4a²-14

2009-10-07T16:43:28+02:00
C) -2x*(-3xy)= 6x kwadrat y
d) x-x/2 - x/3= 3x-3x-2x/6 = - 2x/6
e) -4 * (-x/2) * (- 2x/4)= -4 * 2x kwadrat/8 = - 2xkwadrat / 2
= - x kwadrat
g) -(x+1) + (2x+4)= -x -1 +2x + 4 = x + 3
h) 3(a kwadrat - 4)-(-a kwadrat+ 2)= 3a kwadrat - 12 + a kwadrat -2 = 4 a kwadrat - 14